Relationship between Intensity of Instagram Use and Body ImageIn Adolescents - Vhilyan, Anggita; Mardliyah, Afifah; Novenasari, Ismi (Lafadz Jaya Publisher, 2024)
Information technology in the era of globalization is developing rapidly in people's lives. One of the social media that is popular, especially among teenagers and is widely accessed on smartphones, is Instagram. The use of social media Instagram has a negative impact so that it can worsen body image. This research aims to determine the relationship between the intensity of Instagram use and body image in adolescents. This research uses quantitative methods and sampling is carried out using proportionate stratified random sampling technique. The total population is 190 students at Beringin Ratu High School. The sample size was 78 students. The data analysis method used is Pearson product moment correlation with computer assistance, namely using statistical packages for social science (SPSS) 21.0 for Windows release.The results of data analysis show a correlation (r) of -0.390 with p = 0.000 (p < 0.05). This proves that there is a relationship between the intensity of Instagram use and body image and it has a negative direction. The higher the intensity of Instagram use, the more negative the level of body image and vice versa, so the hypothesis proposed by the researcher is accepted.